Improving b2c e-commerce trust through social presence factors - Che Lah, Nur Syadhila (2013)
In e-Commerce field, there are many researchers conducted on different properties of trust but lack of attention has been given to interpersonal based trust. This has lead to limitations for e-Commerce growth where social events have not yet fully duplicate into digital form especially in e-Commerce environment. Taking the advantage of rapid growth of social network nowadays, the objective of this study is to improve current e-Commerce implementation through social presence. In order to achieve this objective, this study has explored e-Commerce trust properties with its attributes as suggested by previous researchers. Trust factors based on social presence attributes also have been identified. This research hopes to provide a guideline to online businesses in order to develop a trusted website based on updated trend of e- Commerce which is more customer-oriented.